Self Efficacy Pengerjaan Skripsi Prokrastinasi Akademik pada Mahasiswa Fakultas Farmasi Universitas Katolik Widya Mandala Surabaya - Hapsari, Elisabet Widyaning (Universitas Katolik Widya Mandala Surabaya, 2016)
Menyelesaikan pendidikan tinggi merupakan harapan setiap mahasiswa. Untuk meraih jenjang sarjana, mahasiswa harus menyelesaikan tugas-tugas dan menulis skripsi. Selama penulisan skripsi, mahasiswa dapat menjumpai halangan yang membuat mereka melakukan prokrastinasi akademik. Prokrastinasi akademik merupakan penghambat menyelesaikan tugas-tugas akademik. Completing higher education is an expectation of all students. In order to obtain bachelor’s degree, students need to do assignments and write thesis. During thesis writing, students can experience obstacles that lead them to perform academic procrastination. Academic procrastination is a delay for completing academic tasks. Academic procrastination could be caused by self-efficacy. This research aimed to examine correlation between academic procrastination and self efficacy; where self-efficacy is defined as a belief in one’s abilities to perform a task. Students in this study (N=30) were the students at the Faculty of Pharmacy, Widya Mandala Catholic University Surabaya who were doing their thesis. The sampling method was incidental sampling . Data were collected from 42 item scale. It was based on Likert’s scale consisting of academic procrastination scale and self efficacy scale. Data were analyzed using Kendal’s Tau B. The results showed a negative correlation between academic procrastination and self-efficacy with the r value of -0.378 and p = 0.005 (p